(untitled) (Journal of Economic Research & Business Administration, 2016)
In recent years, urban renewal ideas gained new momentum thanks to the mainstreaming of social objectives. One concept, where you can find answers to many questions of urban development is the concept of «creative cities». This concept can give a new quality and content of the measures aimed at the revival of urban areas. This concept changes the traditional concept of urban development. «Creative City» recognizes, nurtures, attracts and supports the talents so that he is able to mobilize the ideas, talents and creative ideas, the conditions for the planning and actions of people with imagination in solving the serious urban problems. The difference between the concept of the «creative city» in that it draws attention to the potential of the cultural heritage and cultural environment. This article attempts to examine the main directions of development of creative industries and the concept of the «creative city» as the driving force of urban development.There are given the data on the dynamics of the revenue in the industry and dynamics, they create jobs. Made a short review of the development of cultural and creative industries, at the regional level by countries of the world.